2017
DOI: 10.15744/2454-4981.3.106
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives of Adult High-Functioning Autism Support Groups’ Use of Neurodiversity Concept

Abstract: Ample research has examind the impact of autism for children and families, but less has addressed the effects of this condition for adults. The literature indicates that adults on the autism spectrum suffer from depression and have a heightened risk of suicidal ideation because of their social skills deficits [1]. Research also shows that individuals with high-functioning autism (HFA) can benefit from participating in support groups. In addition, research indicates that use of the term "neurodiversity" rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 122 publications
0
4
0
Order By: Relevance
“…For instance, in describing the study she conducted with clinicians to assess the hypothetical utility of using a neurodiversity framework as a "therapeutic modality" in clinician-led support groups, psychology scholar Barnhart claims that she "approached this research question as the first step in making direct, positive change in the lives of adults with HFA [high-functioning autism]" (2017, 2) -as if Autistic self-advocates are not decades into fighting for their own civil rights and require help from (presumably neurotypical) researchers and clinicians. Further underscoring this point, Barnhart (2017) goes on to claim that clinician group facilitators are in a position to "introduce" Autistic people to a "new" concept -neurodiversity -the embracing of which can also "lead to more research opportunities, and thus more publications and presentations as research on the topic increases" (2017,6). What, other than institutional power, grants academics with limited or no personal connection to neurodiversity the right to insert themselves into decades-old, activist-led conversations and position themselves as experts?…”
Section: Discussion: Authorities Claims and Conflictsmentioning
confidence: 99%
See 1 more Smart Citation

Weighing In

Livingstone,
Gibson,
Douglas
et al. 2023
IJDSJ
“…For instance, in describing the study she conducted with clinicians to assess the hypothetical utility of using a neurodiversity framework as a "therapeutic modality" in clinician-led support groups, psychology scholar Barnhart claims that she "approached this research question as the first step in making direct, positive change in the lives of adults with HFA [high-functioning autism]" (2017, 2) -as if Autistic self-advocates are not decades into fighting for their own civil rights and require help from (presumably neurotypical) researchers and clinicians. Further underscoring this point, Barnhart (2017) goes on to claim that clinician group facilitators are in a position to "introduce" Autistic people to a "new" concept -neurodiversity -the embracing of which can also "lead to more research opportunities, and thus more publications and presentations as research on the topic increases" (2017,6). What, other than institutional power, grants academics with limited or no personal connection to neurodiversity the right to insert themselves into decades-old, activist-led conversations and position themselves as experts?…”
Section: Discussion: Authorities Claims and Conflictsmentioning
confidence: 99%
“…For others, it's a scientific or ecological concept that points to the genetic and phenotypical diversity of the human species (e.g., Masataka, 2017). For still others, neurodiversity is a pedagogy (e.g., Fitzwater, 2017), a theory (e.g., Tomlinson and Newman, 2017), a paradigm (e.g., Kapp, 2020), an analytical lens (e.g., Bakan, 2014), a portmanteau (Fitzwater, 2017), a framework for disability (Lambert et al, 2020), or even a therapeutic modality (Barnhart, 2017).…”
Section: What Is Neurodiversity?mentioning
confidence: 99%

Weighing In

Livingstone,
Gibson,
Douglas
et al. 2023
IJDSJ
“…More broadly, the practice of autism ‘acceptance’ has recently been associated with increased well‐being in both autistic individuals 59 and family members 60 . Further, research by Gwendolyn Barnhart suggested that clinicians found the neurodiversity concept useful for helping their clients cultivate self‐esteem 61 …”
Section: Reclamation and Pridementioning
confidence: 99%
“…60 Further, research by Gwendolyn Barnhart suggested that clinicians found the neurodiversity concept useful for helping their clients cultivate self-esteem. 61 More positively, to fully incorporate a neurodiversity perspective into therapeutic practice, a focus on neurodivergent pride and disability pride should be exploredincluding as a way to counteract internalized stigma, which is the internalization of the abundance of negative messages minorities receive about their identity. 62,63 Internalized stigma is particularly insidious in that although it is the result of stigmatizing and marginalizing encounters, it can become self-sustaining even without the presence of these events, 64 and it is particularly predictive of poor mental health and higher psychological distress in autistic people.…”
Section: R Ecl a M Ation A N D Pr Idementioning
confidence: 99%